Retinal Angiogenesis Is Mediated by an Interaction between the Angiotensin Type 2 Receptor, VEGF, and Angiopoietin - Sarlos, Stella (American Society for Investigative Pathology, 2003)
There is evidence that angiotensin II, vascular endothelial growth factor (VEGF), angiopoietins, and their cognate receptors participate in retinal angiogenesis. We investigated whether angiotensin type 2-receptor blockade (AT2-RB) reduces retinal angiogenesis and alters the expression of VEGF/VEGF-R2 and angiopoietin-Tie2. Retinopathy of prematurity (ROP) was induced in Sprague Dawley (SD) rats by exposure to 80% oxygen from postnatal (P) days 0 to 11, followed by 7 days in room air. ROP shams were in room air from P0–18. A group of ROP rats received the AT2-RB, PD123319, by mini-osmotic pump (5 mg/kg/day) from P11–18 (angiogenesis period). Evaluation of the retinal status of the AT2 receptor indicated that this receptor, as assessed by real-time PCR, immunohistochemistry, and in vitro autoradiography, was present in the retina, was more abundant than the AT1 receptor in the neonatal retina, and was increased in the ROP model. AT2-RB reduced retinal angiogenesis. VEGF and VEGF-R2 mRNA were increased in ROP and localized to blood vessels, ganglion cells, and the inner nuclear layer, and were decreased by PD123319. Angiopoietin2 and Tie2, but not angiopoietin1 mRNA were increased with ROP, and angiopoietin2 was reduced with PD123319. This study has identified a potential retinoprotective role for AT2-RB possibly mediated via interactions with VEGF- and angiopoietin-dependent pathways.